The "dwelling of the lion" on the ways of Horus - Hoffmeier, James Karl; Kitchen, Kenneth A. (Eisenbrauns, 2014)
Introduction to the work at Tell el-Borg /James K. Hoffmeier --"The ways of Horus" : reconstructing Egypt's east frontier defense network and the military road to Canaan in New Kingdom times /James K. Hoffmeier and Stephen O. Moshier --The geological setting of Tell el-Borg with implications for ancient geography of northwest Sinai /Stephen O. Moshier --Field I and miscellaneous inscriptions /James K. Hoffmeier and Kenneth A. Kitchen --The fortification area /James K. Hoffmeier, James E. Knudstad, Rosa A. Frey, Ronald D. Bull, and Gregory D. Mumford --The Ramesside Period fort /James Hoffmeier, James E. Knudstad, Rosa Frey, Gregory Mumford, and Kenneth A. Kitchen --Results of the magnetic survey at Tell el-Borg, North Sinai, March 2006 and 2007 /Tomasz Herbich --A report on the ceramics recovered from Tell el-Borg /Rexine Hummel --Levantine-Egyptian interconnections at Tell el-Borg, North Sinai /Catherine A. Duff --The Cypriot pottery /Stuart Swiny --Ceramic miscellanies : preliminary report on the Mycenaean pottery /Rexine Hummel --Metal weapons from Tell el-Borg : the spear/lance (TBO 0177) and sword (TBO 0395) from field IV /Mike Neska.